To be understood: Transitioning to adult life for people with Autism Spectrum Disorder - Thompson, C.; Bolte, Sven; Falkmer, Torbjorn; Girdler, Sonya (Public Library of Science, 2018)
Introduction: The purpose of this study was to explore the viewpoints of parents of young people with Autism Spectrum Disorder (ASD) in relation to their child's transition to adulthood. Methods: Data were collected during four structured focus groups with 19 parents of young people with ASD with average to high intellectual capacities. Condensed meaning units were identified and checked during focus groups, and were subsequently linked to the International Classification of Functioning, Disability and Health (ICF). Results: Three major themes emerged: to be understood, to understand the world and to succeed. The ICF domains of activity and participation and environmental factors emerged as having the greatest potential to influence transition outcomes. Conclusions: Policies and services should focus on strengths to maximise participation in higher education, employment and independent living amongst young people with ASD. Interventions targeting environmental factors could be effective in improving participation in adult life. Person-centred and individualised approaches could further complement this approach supporting the transition to adulthood for people with ASD, ultimately improving outcomes in adulthood.